Upaya Meningkatkan Kreativitas Peserta Didik dengan Memanfaatkan Model Pembelajaran Konstruktivisme dengan Metode Diskusi dalam Pembelajaran PPKN pada Kelas VII SMP Sunan Giri Probolinggo - Dzaky Isyuniandri; Erika Fara Septia Ningrum; Urnika Ainurrohmah; Moh. Adzib Zamroni; Samsul Arifin (Journal Innovation In Education, 2025)
This research aims to describe increasing student creativity in Civics learning using the discussion method in class VII students at Sunan Giri Middle School, Probolinggo. This type of research is classroom action research. The subjects of this research were students of class VII Sunan Giri, with a total of 16 students consisting of 7 male students and 9 female students. Meanwhile, the object of this research was Civics learning activities using the Constructivist Learning model. Data collection methods in this research used tests, observation and documentation. The indicators for the success of this action research were determined to be increasing student creativity in the very active category by 80% of the total number of students. The results of research on PPKn learning using the discussion method can increase student learning creativity. And it can be seen from the results of implementing actions using the discussion method to increase student creativity in PPKn subjects, where activity has reached 87.5%, which means that student activity has reached the specified indicators. namely 80%. Thus, the discussion method can increase student learning creativity in Civics subjects in class VII students at Sunan Giri Middle School, Probolinggo.